The tragedy of the common holdings: Coordination strategies and product market competition - Werner Neus; Manfred Stadler (University of Tübingen, Faculty of Economics and Social Sciences, 2022)
We study quantity and price competition in heterogeneous triopoly markets where two firms are commonly owned by institutional shareholders, whereas the third firm is owned by independent shareholders. With such a mixed ownership structure, the common owners have an incentive to coordinate their firms' behavior. If direct coordination of the operational decisions is prevented by antitrust authorities, delegation to managers enables indirect coordination via the designs of the manager compensation contracts. Compared to direct owner collusion, this more sophisticated type of indirect collusion leads to a lower loss of social welfare in the mode of quantity competition, but to a higher loss of welfare in the mode of price competition. In general, owner coordination via the management compensation contracts is detrimental to welfare: the tragedy of common holdings.
urn:nbn:de:bsz:21-dspace-1299028; hdl:10900/129902
Keywords: G32; L22; M52; 330; Manager compensation; common holdings; shareholder coordination